2004
DOI: 10.1103/physrevlett.93.186806
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Sensitivity to Dephasing of Electrical Conduction Through a Quantum Dot

Abstract: According to random-matrix theory, interference effects in the conductance of a ballistic chaotic quantum dot should vanish ∝ (τ φ /τD) p when the dephasing time τ φ becomes small compared to the mean dwell time τD. Aleiner and Larkin have predicted that the power law crosses over to an exponential suppression ∝ exp(−τE/τ φ ) when τ φ drops below the Ehrenfest time τE. We report the first observation of this crossover in a computer simulation of universal conductance fluctuations. Their theory also predicts an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…For an open version of the quantum kicked rotator map, numerical simulations were reported for shot noise, 8,9,10 weak localization, 11,21 and universal conductance fluctuations. 9,18,22 Simulation results for shot noise were in good agreement with the predictions of the semiclassical theory. 6 However, for conductance fluctuations, no dependence on τ E was found, despite the fact that Ehrenfest times larger than the dwell time were considered.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…For an open version of the quantum kicked rotator map, numerical simulations were reported for shot noise, 8,9,10 weak localization, 11,21 and universal conductance fluctuations. 9,18,22 Simulation results for shot noise were in good agreement with the predictions of the semiclassical theory. 6 However, for conductance fluctuations, no dependence on τ E was found, despite the fact that Ehrenfest times larger than the dwell time were considered.…”
supporting
confidence: 74%
“…However, semiclassical theories for weak localization and universal conductance fluctuations for the limit τ D ≫ τ E are essentially equal, 14,15,16,17 as are diagrammatic perturbation theories for the same phenomena in diffusive cavities, supporting the expectation that the Ehrenfest-time dependencies of weak localization and universal conductance fluctuations will be equal as well. 18 Direct numerical simulation of the effect of a large Ehrenfest time on quantum transport through twodimensional chaotic cavities has been problematic because of the prohibitively high computational cost of the simulations. The reason is that τ E depends only logarithmically on the product of the electron wavenumber k and the cavity size L, τ E = λ −1 ln kL.…”
mentioning
confidence: 99%
“…5, has received much theoretical support in the context of transport. 18,27,[30][31][32][33][34] The present work shows that it can be successfully used to describe the consequences of time-reversal-symmetry breaking on the superconducting proximity effect.…”
Section: Discussionmentioning
confidence: 99%
“…(7), with τ φ,ball replaced by τ φ , for a quantum dot in which dephasing arises from a voltage probe ballistically coupled to the dot [22]. Tworzydlo et al, who considered a tunnel-coupled voltage probe, reported δG ∝ exp(−τ E /τ φ ) based on an 'effective random matrix theory' which neglects the second passage through the Lyapunov region [23]. The correct result for dephasing from a tunnel-coupled voltage probe is δG ∝ exp(−2τ E /τ φ ) [16,22].…”
mentioning
confidence: 99%